Virtual Internationalization in Higher Education - Bruhn, Elisa (wbv Media, 2020)
Digital media and information and communication technology (ICT) are being used more and more in international contexts at universities. In her English-language dissertation, Elisa Bruhn examines how this technological potential can be used strategically to expand internationalization. The data basis of the thesis is a content analysis of contributions to international conferences on university internationalization, online and distance learning, university management and research, and ICT and internationalization. The selected abstracts were analyzed based on the model of "Comprehensive Internationalization" (CI). From the results, Bruhn outlines a model for Virtual Internationalization (VI) that considers curricula, international cooperation, and distance learning as well as the roles of university strategy, administration, management, and teaching staff. The highly topical dissertation closes a gap in university research and offers universities valuable starting points in research and practice of internationalization. Digitale Medien und Informations- und Kommunikationstechnologie (IKT) werden mehr und mehr in internationalen Kontexten an Hochschulen eingesetzt. Wie dieses technologische Potenzial strategisch für den Ausbau von Internationalisierung eingesetzt werden kann, untersucht Elisa Bruhn in ihrer englischsprachigen Dissertation. Die Datenbasis der Arbeit bildet eine Inhaltsanalyse von Beiträgen zu internationalen Konferenzen zur Hochschul-Internationalisierung, zu Online- und Fernstudium, Hochschulmanagement und -forschung sowie zu den Themen IKT und Internationalisierung. Die ausgewählten Abstracts wurden auf Grundlage des Modells der "Comprehensive Internationalization" (CI) analysiert. Aus den Ergebnissen skizziert Bruhn ein Modell für Virtuelle Internationalisierung (VI), das Curricula, internationale Kooperationen und den Bereich Fernstudium ebenso berücksichtigt wie die Rollen von Hochschulstrategie, Administration, Management und Lehrpersonal. Die hochaktuelle Dissertation schließt eine Lücke in der Hochschulforschung und bietet Hochschulen wertvolle Ansatzpunkte in Forschung und Praxis der Internationalisierung.